Impact of Occupational Musculoskeletal Disorders on Dentists: Occupational Musculoskeletal Disorders on Dentists - Shakoor , Asma; Saba Khan, Aleshba; Naz, Fariha; Ali , Waqar; Sultan, Dilawar; Ahmad, Maaz (Pakistan Journal of Health Sciences, 2022)
Dentists are particularly vulnerable to ergonomically borne musculoskeletal diseases (MSDs), which decrease efficiency, productivity, and career longevity because to the exact and minute nature of their work. Objective: To determine different consequence of work related disorders among dentist of Lahore, Pakistan. Methods: In this cross-sectional survey 450 dentist of Lahore were approached and a structured proforma based survey was conducted using convenience sampling technique. In the study, dentists between the ages of 24 and 65 were included. Musculoskeletal Disorder has been presented in the form of frequency and percentage whereas age has been shown as mean and standard deviation. Chi square test has been applied to determine the association between musculoskeletal disorder and different study variables. P-value of 0.05 has been deemed significant. Results: In this study out of 450 dentists 236 (52.4%) were male and 214 (47.6%) were females. Mean age of the males were 37.08 ± 9.27 years and females were 33.43 ± 10.42 years. Among the subject’s musculoskeletal disorders were reported by 393(87.3%) dentist. Sick leave was availed by 278 (70.7%) whereas 373 (94.9%) seek medical treatment and 325 (82.7%) prevent daily activity. According to Dentist 388 (98.7%) believes that the disorder is caused by Dental Clinic I.e. Ergonomic issue. Conclusions: With two thirds of dentists taking sick time owing to musculoskeletal disorders, combined with the mental stress, it would appear that dentistry is not an easy profession. This would significantly limit the career of dentists.